THE IMPACT OF EXPLICIT TEACHING OF SELF-QUESTIONING STRATEGY ON THE ELEVENTH GRADE STUDENTS' READING COMPREHENSION OF BIOGRAPHICAL TEXT - ., Ni Kadek Novi Susian Dewi; ., I Nyoman Pasek Hadi Saputra, S.Pd., M.Pd; ., I Putu Ngurah Wage Myartawan, S.Pd., M.P (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian deskriptif kualitatif ini bertujuan untuk mengetahui pengaruh explicit teaching of self-questioning strategy terhadap kemampuan membaca siswa kelas sebelas dalam membaca teks biografi. Populasi penelitian ini adalah siswa kelas sebelas SMAN 3 Singaraja Tahun Ajaran 2016/2017. Sample penelitian ini terdiri dari 30 siswa kelas 11 di SMAN 3 Singaraja. Siswa menerima pengajaran dengan explicit teaching of self-questioning strategy yang mendorong pengaplikasian strategi self-questioning dalam proses membaca. Tes pilihan ganda diberikan di akhir perlakuan untuk pengumpulan data penelitian. Data yang didapat dari hasil post-test dianalisis menggunakan analisis statistik deskriptif. Temuan penelitian ini menunjukkan bahwa pengimplementasian explicit teaching of self-questioning strategy berdampak terhadap kemampuan membaca siswa secara keseluruhan dan berdampak paling besar terhadap kemampuan siswa dalam membuat prediksi berdasarkan informasi dalam bacaan dan kemampuan siswa dalam menarik kesimpulan dari informasi dalam bacaan. Oleh sebab itu, explicit teaching of self-questioning strategy adalah salah satu pengajaran yang efektif untuk meningkatkan kemampuan membaca siswa dan pengimplementasiannya disarankan bagi guru untuk meningkatkan kempuan membaca siswanya.Kata Kunci : kemampuan membaca, explicit teaching, self-questioning This descriptive qualitative study aimed at finding out the impact of explicit teaching of self-questioning strategy on eleventh grade students’ reading comprehension of biographical text. The population of the study was eleventh grade students of SMAN 3 Singaraja in Academic Year 2017/2018. The sample consisted of 30 students of an intact class which were randomly assigned as the sample of the study. In this study, the students received an explicit teaching of self-questioning strategy which encourages them to use the reading strategy in their reading class. Multiple choice tests were administered at the end of the treatment to collect the research data. The data obtained through post-test were analyzed quantitatively by using descriptive analysis. The findings showed that the implementation of explicit teaching of self-questioning strategy had an impact on students' reading comprehension of biographical text in which it gives impact on students’ overall comprehension especially on students’ ability in making prediction based on information provided in the text and drawing conclusion. Consequently, explicit teaching of self-questioning can be implemented for improving students’ reading comprehension and its implementation is suggested to teacher for improving their students’ reading comprehension. keyword : reading comprehension, explicit teaching, self-questioning